Hands-on deep learning algorithms with Python : master deep learning algorithms with extensive math by implementing them using TensorFlow - Ravichandiran, Sudharsan (Packt Publishing Ltd, 2019)
This book introduces basic-to-advanced deep learning algorithms used in a production environment by AI researchers and principal data scientists; it explains algorithms intuitively, including the underlying math, and shows how to implement them using popular Python-based deep learning libraries such as TensorFlow.